The Vision of Lithuania in the Lithuanian Anti-Nazi Press - Venclauskas, Linas (Genocidas ir rezistencija, 2004)
The aim of this article is to introduce the vision of Lithuania and ways to achieve statehood as presented by different Lithuanian underground publications of the Second World War. It also seeks to give a more detailed analysis of the content in the articles themselves, their contradictions, ideological principles, and attitudes towards the minorities. Although the revolt of June 1941 failed to reach its goal, the restoration of Lithuanian independence, the idea itself was not surrendered. The historiography agrees that the LAF (the Lithuanian Activists’ Front) managed to enlist the main Lithuanian political powers for the restoration of statehood. However, after the uprising, those forces scattered again and acted in smaller or bigger units in the underground, until in 1943 they again succeeded in uniting into the Supreme Committee for the Liberation of Lithuania (VLIK) which expressed the most explicit (in 1944) image of independent Lithuania. In the VLIK, the political powers with completely different prospects managed to come to an agreement and a common ideology, thus creating real basis for acting together. However, the VLIK project was also utopian, in the sense that the predictions of Lithuanians concerning the end of the Second World War did not prove accurate.